Relational autonomy in breast diseases care: a qualitative study of contextual and social conditions of patients’ capacity for decision-making - Patti Shih; Frances Rapport; Anne Hogden; Mia Bierbaum; Jeremy Hsu; John Boyages; Jeffrey Braithwaite (BMC Health Services Research, 2018)
Abstract Background A relational approach to autonomy refers to the way in which social conditions and relationships shape a person’s self-identity and capacity in decision-making. This article provides an empirical account of how treatment choices for women undergoing breast diseases care are fostered within the dynamics of their relationships with clinicians, family members, and other aspects of their social environment. Methods This qualitative study recruited ten women undergoing treatment at a breast programme, and eight clinicians supporting their care, in a private teaching hospital in New South Wales, Australia. Fourteen patient-clinician consultation observations and 17 semi-structured interviews were conducted. Schema analysis of interview transcripts were undertaken by a team of researchers and corroborated by observational fieldnotes. Results Relational identities of patients influenced the rationale for treatment decision-making. Patients drew on supportive resources from family and medical advice from clinicians to progress with treatment goals. While clinicians held much social power over patients as the medical experts, patients highlighted the need for clinicians to earn their trust through demonstrated professionalism. Information exchange created a communicative space for clinicians and patients to negotiate shared values, promoting greater patient ownership of treatment decisions. As treatment progressed, patients’ personal experiences of illness and treatment became a source of self-reflection, with a transformative impact on self-confidence and assertiveness. Conclusion Patients’ confidence and self-trust can be fostered by opportunities for communicative engagement and self-reflection over the course of treatment in breast disease, and better integration of their self-identity and social values in treatment decisions.